Catalytic Change of C1-C4-Alkanes - N.I. Fayzullaev, S.Yu. Bobomurodova, G.A. Avalboev, M.B. Matchanova, Z.T. Norqulova (International Journal of Control and Automation, 2020)
The catalytic changes in C1-C4 hydrocarbons were studied in a flow reactor made of steel with an internal diameter of 12 mm at atmospheric pressure, within the temperature range of 550-6500C, with a volumetric rate of the mixture of reagents 175-350 ml / min and contact time 0.5-17.0 sec The acid properties of the catalysts were studied by thermogravimetric desorption of ammonia. The structure and state of the active sites of the catalyst were studied by electron microscopy, and its surface by the BET method. The maximum yield of aromatic hydrocarbons from C1-C4 hydrocarbons is observed on a catalyst of the composition (MoO3)x ∙ (ZnO)y ∙ (ZrO2)z ∙ (B2O3)k.